Criação de um portfólio de cursos de extensão para o Campus Itaituba da Universidade Federal do Oeste do Pará - Oliveira, Erinaldo Silva (2019)
The present dissertation, titled - "Creating a portfolio of extension courses for Campus Itaituba the Federal University of Western Pará" - had as objective to create a portfolio of extension courses to work as a guidance instrument and relational development in the effort of the Federal University of the West of Pará (Ufopa) Campus Itaituba to supply the needs of the environment in which it operates. The scientific-technological method was used, which began with the construction of scientific knowledge, whose first stage was the definition of state-of-the-art, followed by the collection, organization and generation of the knowledge required for the realization of technological production. The construction of the prototype of the product (portfolio) was its first stage, followed by the tests and retests of the prototype until the validation of the final product, its last stage. The results obtained with the empirical survey were: a) offer of the courses of Attendance to the Public, Administrative Assistants, Sales Techniques, Business Management and Human Resources, b) identification of training needs of components of the productive sector and environmental services to which Itaituba Campus is located c) formative satisfaction of 22 inhabitants of the Campo Verde district in Itaituba d) identification of new niches of action for the extension sector of the Itaituba Campus, e) closer relationship between university and other components of the environment. The product complied adequately the mediating function of the institution's relationship with its environment of acting as a provider of needs, because it identifies partnerships; have contributed to the development and citizenship in the Amazon; be an excellent means of institutional communication; allow the identification and updating of the courses that the environment desires, exposing in its structure what the environment needs and what Ufopa is able to offer, deepening the institutionalization and making it possible for the training actions to be focused with a high probability of success. The contribution of the product to the EPT area is new proposals for fast, dynamic and efficient professional courses, together with the presentation of a product that aims to help fulfill one of the pillars of the EPT organizations that is to help to solve the environmental problems of the area in which they are inserted.